Drosophila p53 is a structural and functional homolog of the tumor suppressor p53. - Ollmann, M.; Young, L.M.; Di Como, C.J.; Karim, F.; Belvin, M.; Robertson, S.; Whittaker, K.; Demsky, M.; Fisher, W.W.; Buchman, A.; Duyk, G.; Friedman, L.; et al. (Cell, 2000)
The importance of p53 in carcinogenesis stems from its central role in inducing cell cycle arrest or apoptosis in response to cellular stresses. We have identified a Drosophila homolog of p53 ("Dmp53"). Like mammalian p53, Dmp53 binds specifically to human p53 binding sites, and overexpression of Dmp53 induces apoptosis. Importantly, inhibition of Dmp53 function renders cells resistant to X ray-induced apoptosis, suggesting that Dmp53 is required for the apoptotic response to DNA damage. Unlike mammalian p53, Dmp53 appears unable to induce a G1 cell cycle block when overexpressed, and inhibition of Dmp53 activity does not affect X ray-induced cell cycle arrest. These data reveal an ancestral proapoptotic function for p53 and identify Drosophila as an ideal model system for elucidating the p53 apoptotic pathway(s) induced by DNA damage.